Analisis Kinerja Keuangan PT. Pembangunan Jaya Ancol Tbk. Pada Masa Pandemi Covid-19 Tahun 2020-2021 - Musdalifa Musdalifa; Fitri Kumalasari; Agus Zul Bay (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2023)
This study aims to determine: The success rate of the financial performance of PT. Pembangunan Jaya Ancol Tbk., during the 2020-2021 Covid-19 Pandemic when viewed from an analysis of financial ratios. The analytical tool used is financial ratio analysis which includes liquidity ratios, solvency ratios, profitability ratios and activity ratios. This research is qualitative research with a descriptive approach using calculations on quantitative data in the form of year-end closing financial reports (secondary data) from 2020-2021. In general, the results of financial performance analysis using ratio analysis from the perspective of liquidity ratios show that during the Covid-19 pandemic, PT. Pembangunan Jaya Ancol Tbk., was able to fulfill its short-term obligations in a timely manner, viewed from a solvency perspective, showing that during the Covid-19 pandemic PT. Pembangunana Jaya Ancol Tbk. able to guarantee financing its debt obligations with a number of assets owned by the company's capabilities as described by capital (equity), viewed from a profitability perspective, shows that PT is inefficient and ineffective. Pembangunan Jaya Ancol Tbk., in utilizing and using company assets to generate profits during the Covid-19 pandemic, while viewed from an Activity perspective, shows that PT. Pembangunan Jaya Ancol Tbk., during the Covid-19 pandemic was effective in using and controlling its resources.